Tear film parameters and meibography in eyes of children with vernal keratoconjunctivitis - Ruchi Gupta; Ritu Arora; Isha Gupta; Parul Jain (Indian Journal of Ophthalmology)
Purpose: To study tear film parameters and Meibomian glands in pediatric patients with vernal keratoconjunctivitis (VKC). Methods: Forty-four eyes of 22 patients with VKC and 44 eyes of 22 age-matched controls were studied in a hospital-based cross-sectional study. Each subject underwent a complete ophthalmological examination including slit-lamp biomicroscopy, non-invasive break-up time (NIBUT), fluorescein break-up time (FBUT), corneal fluorescein staining, and Schirmer’s test. Non-contact meibography was performed using a Sirius topographer. Results: All patients had VKC grades between 1 and 3 (Bonini scale). The mean NIBUT for cases was 8.83 ± 4.02 s and in controls, it was 15 ± 2.8 s (P value < 0.001). The mean FBUT for cases was 9.41 ± 3.45 s and in controls, it was 16.7 ± 2.5 s (P value < 0.001). Schirmer’s values were 32 ± 3.1 mm in cases and 21.4 ± 4.1 mm in controls, which were significantly higher (P value < 0.001). Also, 22.72% of the cases had corneal fluorescein staining in the form of superficial punctuate keratitis, whereas none of the control groups showed corneal staining. The examination of Meibomian glands using non-contact meibography showed a mean Meibomian gland dropout in the upper lid to be 29.7 ± 14.4% in VKC cases and 10.5 ± 3.2% in controls (P value < 0.001). Meibography of the lower lid showed 25.9 ± 10.2% dropout in cases and 20.5 ± 6.1% in controls (P value = 0.004). Conclusion: Tear film parameters were significantly deranged in children with VKC in the active stage as compared to age-matched controls. Children with VKC also had a higher Meibomian gland dropout.